Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru - Marianita Marianita; Army Yuneti (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of the study is to improve teacher performance in SMA Negeri 4 Lubuklinggau, how is the principle of increasing teacher permormance. The research method used is descriptive study, observation and documentation, and this study also uses a type of procedure to develop materials. The results of research on principals have implemented leadership strategies well, by discussing the conditions and conditions of teachers, creativity in applying leadership styles, having tips and having motivations that improve to improve teacher performance. The conclusion of this study is that this study is used to improve the performance of high school students, and have high motivation to improve teacher performance. Keywords: Principle Strategy, Improve Teacher Performance